KESESUAIAN LAHAN PEMUKIMAN PADA LAHAN SAWAH DI KECAMATAN JUWANA KABUPATEN PATI - Zebyan, Denny; Sunarko, Sunarko; Suroso, Suroso (Geo-Image, 2016)
Selection of an appropriate location for the settlement of significant importance in the spatial aspect, because mentukan durability of the building, economic value, and the impact of settlements on the surrounding environment (Sutikno, 1982). issues to be examined is whether the wetland is converted to residential land in the District of Pati regency Juwana according to land suitability settlement. Of these problems, this study aims to determine the suitability of residential land on the former wetland in District JuwanaPati regency. The area that became the object of research is the District JuwanaPati regency, which includes 27 villages that will be used as a study area, a source of research data kemiringinan slope and depth of the groundwater, such as data collection methods: observation and documentation, data analysis technique by describing. Based on the data obtained to determine the suitability class residential land in District Juwana. The results obtained, discussions were held on the following results in the District Land Condition Juwana only has one class of slope, and two classes depth of the groundwater. For land suitability classes based on research data can be seen that the District Juwana has one class of residential land suitability ie S1 (very appropriate).